Evolutionary shifts in the thermal biology of a subterranean mammal: the effect of habitat aridity - Merchant, H; Hart, D; Bennett, N; Janse van Vuuren, A; Freeman, M; McKechnie, A; Faulkes, C; Mordaunt, N; Portugal, SJ (Company of Biologists, 2024)
Subterranean mammals representing a single subspecies occurring along an aridity gradient provide an appropriate model for investigating adaptive variation in thermal physiology with varying levels of precipitation and air temperature (Tair). This study examined the thermal physiological adaptations of common mole-rats (Cryptomys hottentotus hottentotus) across five populations along an aridity gradient, challenging the expectation that increased aridity would lead to reduced metabolic rate (MR), lower body temperatures (Tb), and broader thermoneutral zones (TNZ). Contrary to predictions, no significant, consistent differences in MR, Tb, or thermal conductance were observed between populations, suggesting uniform thermoregulatory mechanisms across habitats. Instead, behavioral strategies such as huddling and torpor may play a more prominent role than physiological adaptations in managing temperature regulation and water balance. The study also observed osmoregulatory differences, with populations employing distinct behavioral cooling strategies in response to water availability. These results underscore the need for further research into the responses of subterranean species to climate change, particularly in understanding how increasing global temperatures and aridification might influence species distribution if they lack the physiological capacity to adapt to future climatic conditions.